Subject position affects EEG magnitudes - Rice, Justin K.; Rorden, Christopher; Little, Jessica S.; Parra, Lucas C. (NeuroImage (Orlando, Fla.), 2013)
EEG (electroencephalography) has been used for decades in thousands of research studies and is today a routine clinical tool despite the small magnitude of measured scalp potentials. It is widely accepted that the currents originating in the brain are strongly influenced by the high resistivity of skull bone, but it is less well known that the thin layer of CSF (cerebrospinal fluid) has perhaps an even more important effect on EEG scalp magnitude by spatially blurring the signals. Here it is shown that brain shift and the resulting small changes in CSF layer thickness, induced by changing the subject's position, have a significant effect on EEG signal magnitudes in several standard visual paradigms. For spatially incoherent high-frequency activity the effect produced by switching from prone to supine can be dramatic, increasing occipital signal power by several times for some subjects (on average 80%). MRI measurements showed that the occipital CSF layer between the brain and skull decreases by approximately 30% in thickness when a subject moves from prone to supine position. A multiple dipole model demonstrated that this can indeed lead to occipital EEG signal power increases in the same direction and order of magnitude as those observed here. These results suggest that future EEG studies should control for subjects' posture, and that some studies may consider placing their subjects into the most favorable position for the experiment. These findings also imply that special consideration should be given to EEG measurements from subjects with brain atrophy due to normal aging or neurodegenerative diseases, since the resulting increase in CSF layer thickness could profoundly decrease scalp potential measurements. ► Anatomical MRIs show brain shift with changing subject orientation. ► Multi-dipole model predicts large EEG magnitude changes as a consequence. ► Prone to supine shift selectively enhances EEG signals. ► Gamma activity is increased greatly and consistently.